PENYELESAIAN SENGKETA ANTARA BUMN DENGAN PEMERINTAH DAERAH DALAM PENGELOLAAN ASET DAERAH - diantara, Okta Arwan (Universitas 17 Agustus 1945 Samarinda, 2025)
ABSTRACT. Disputes between state-owned enterprises (SOEs) and local governments in asset management can also arise from differences in legal interpretation. As business entities, SOEs often operate with a profit orientation, while local governments have the responsibility to ensure that assets are used for public interest. This research examines the legal provisions governing the resolution of disputes between SOEs and the factors that lead to disputes between SOEs and local governments in regional asset management. Normative research is a process to find legal rules, legal principles, and legal doctrines to address the legal issues raised, using a legislative approach. The results of the research on the resolution of disputes between state-owned enterprises (BUMN) and local governments in the management of regional assets require an integrated approach based on applicable laws and regulations, such as Law Number 19 of 2003 on State-Owned Enterprises and Law Number 23 of 2014 on Regional Government. Furthermore, disputes between BUMN and local governments in the management of regional assets occur due to various factors, such as unclear asset ownership status, conflicting interests, lack of coordination, and regulatory overlaps. Keywords: Dispute, State-Owned Enterprises, Regional Asset Management.